Blood pressure response to standing is a strong determinant of masked hypertension in young to middle-age individuals. Issue 10 (23rd October 2022) - Palatini, Paolo; Mos, Lucio; Rattazzi, Marcello; Spinella, Paolo; Ermolao, Andrea; Vriz, Olga; Battista, Francesca; Saladini, Francesca
Abstract : Objective: The pathophysiologic mechanisms of masked hypertension are still debated. The aim of this study was to investigate whether the blood pressure response to standing is a determinant of masked hypertension in young individuals. Design and methods: We studied 1078 individuals (mean age 33.2 ± 8.5 years) with stage-1 untreated hypertension at baseline. Orthostatic response was defined as the difference between six SBP measurements in the orthostatic and supine postures. People with a response more than 6.5 mmHg (upper decile) were defined as hyperreactors. After 3 months of follow-up, 24-h ambulatory BP was measured and the participants were classified as normotensives ( N  = 120), white-coat hypertensive individuals ( N  = 168), masked hypertensive individuals ( N  = 166) and sustained hypertensive individuals ( N  = 624). In 591 participants, 24-h urinary epinephrine was also measured. Results: Orthostatic response was an independent predictor of masked hypertension after 3 months ( P  = 0.001). In the whole group, the odds ratio for the Hyperreactors was 2.5 [95% confidence interval (95% CI) 1.5–4.0, P  < 0.001]. In the participants stratified by orthostatic response and urinary epinephrine, the odds ratio for masked hypertension was 4.2 (95% CI, 1.8–9.9, P  = 0.001) in the hyperreactors with epinephrine above the median and was 2.6 (95% CI, 0.9–7.3, P  = 0.069) in those with epinephrine below the median. The association between orthostatic response and masked hypertension was confirmed in the cross-sectional analysis after 3 months ( P  < 0.001). Conclusion: The present findings indicate that hyperreactivity to standing is a significant determinant of masked hypertension. The odds ratio for masked hypertension was even quadrupled in people with an orthostatic response more than 6.5 mmHg and high urinary epinephrine suggesting a role of sympathoadrenergic activity in the pathogenesis of masked hypertension.